Pneumonia in Adults: the Practical Emergency Department Perspective - Woolfrey, Karen G.H. (Emerg Med Clin North Am, 2012)
In those patients who are hospitalized with pneumonia, mortality is 15%. Close to 90% of deaths attributed to pneumonia are in patients older than 65 years. This article provides the emergency physician with an understanding of how to make the diagnosis, initiate early and appropriate antibiotic therapy, risk stratify patients with respect to the severity of illness, and recognize indications for admission. The discussion is balanced with an emphasis on cost-effective management, an understanding of the changing spectrum of pathogenesis, and a cognizance toward variable and less common presentations.